ANALISIS PERANAN DAN DAMPAK INVESTASI INFRASTRUKTUR TERHADAP PEREKONOMIAN INDONESIA: ANALISIS INPUT-OUTPUT - Chandra Darma Permana; Alla Asmara (School of Business, Bogor Agricultural University (SB-IPB), 2010)
Despite being recovered from economic crisis, the infrastructure development in Indonesia still hasn’t shown a significant improvement. It is reflected from the diminishing government allocation for infrastructure as a percentage of Gross Domestic Products. The main objective of the study is to analyze the role of infrastructure through the linkage analysis, dispersion effect analysis, multiplier effect analysis, and the investment effect analysis. The scope of infrastructure is only referred to electricity, gas and water, and construction sector. The data used for this study is the 2005 Indonesian Input-Output Table. The result of the study has shown that infrastructure has a higher backward linkage than its forward. In addition, all of the infrastructure sectors has shown more than one dispersion coefficient and conversely has revealed less than one value for the dispersion sensitivity. Which means that infrastructure had a better capability to support the development of its upstream sectors than its downstream. Infrastructure has a positive multiplier effect toward the other sectors. The growth of the investment in the electricity, gas and water sector has given the biggest effect toward the change of the total outpu, while the water sector has given the biggest effect toward the change in the total income, and road, bridge and port sector has given the biggest effect toward the change in the total labour.